Ability To Distinguish Between Standard Vocabulary And Non-Standard Vocabulary In Indonesian Language Courses For Semester 1 Class F Students At Faculty Of Veterinary Medicine In 2023 - Supriadin, Supriadin; Syarifoeddin, Elya Wibawa; Ikhsan, Muhamad (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Standard words are words that follow linguistic rules recognized in Indonesian. Spelling, conventional grammar, and common dictionary words are just some of the linguistic norms that can be found in standard words. This research aims to describe the level of students' ability to differentiate standard vocabulary from non-standard vocabulary in Indonesian. The population in this study were students in semester 1 (one) class F of the Veterinary Medicine Education Study Program, Faculty of Veterinary Medicine, Mandalika Education University totaling 39 people. Data collection was carried out using test techniques, while data analysis was carried out using percentage techniques. Based on the results of the research that has been carried out, it is known that the level of student ability is adequate. This can be seen from the results of data analysis which shows that 74.36%Sample students who got a score of 6.5 and above, while students who got a score below 6.5 were 25.64%%.On this basis, it is hoped that in the learning process in class, lecturers who teach Indonesian language courses will intensively provide assignments or training to students, especially in terms of the differences between standard and non-standard vocabulary. So that in the end students are able to determine the differences between the two